1 Year outcomes following surgical ligation of the patent ductus arteriosus in premature infants in scotland. (7th June 2011) - Heuchan, A M; Hunter, L; Young, D
Abstract : Objective: Analysis of morbidity, mortality and associated risk factors following ligation of the patent ductus arteriosus (PDA) in premature infants. Methods: Retrospective case note audit of premature infants referred to a national paediatric cardiothoracic surgical service (2001–2007). Results: The study included 125 infants, median gestational age of 26 weeks (IQR 25–27 weeks) and median birth weight of 840 g (IQR 730–1035 g). Referral characteristics included median LA:Ao 1.8 (IQR 1.5–2.0), ventilation (80%), CPAP (18.4%), diuretics (70%) and 58% treated with cyclo-oxygenase inhibitors (COIs). The median age at PDA ligation was 31 days (IQR 25–41 days). Post-operative characteristics included time to extubation 5 days (IQR 3–10 days), 36% required corticosteroids, 46.8% domiciliary oxygen and 4.8% vocal cord palsy. Mortality rates at 30 days and 1 year were 4.8% and 12.8%, respectively, with neurodisability in 32% of survivors. All deaths occurred in the ventilated group and were mainly attributable to bronchopulmonary dysplasia (BPD). Gestation was significantly associated with early death (<30 days). FiO2, ventilation, lack of prior COIs and post-operative corticosteroids were significantly associated with death by 1 year. Pre-operative FiO2 >40% and lack of prior COIs retained independent significance for death at 1 year post-ligation. Conclusions: PDA ligation is well tolerated, with evidence of early benefit. The incidence of neurodisability or death from BPD at 1 year remains high. Increasing pre-operative FiO2 and lack of prior treatment with COIs are associated with an increased risk of death at 1 year.